Evaluating Habitat of Houbara Bustard (Chlamydotis Undulata) Through Trending of Vegetation Activity in Cholistan Desert of Pakistan - Mukhtar, Rabia; Abbas, Sunaina; Saqib, Zafeer; Ashraf, Arshad (International Journal of Environment, 2021)
In the present study, the habitat of Houbara Bustard was evaluated in Lal Suhanra National Park (LSNP) of Cholistan desert, Pakistan using remote sensing data of LANDSAT-5 and MODIS hyper-temporal vegetation index data of 2000-2012 period. Trend analysis of Normalized Difference Vegetation Index was performed using seasonal Mann-Kendall test to understand the distribution and projected status of the habitat. Over 76% area of the LSNP comprising of sand dunes, sandy/open shrubs, sandy (barren) and open shrubs was identified as the most suitable habitat for Houbara. Majority of the LSNP area exhibited stable trend in land cover/vegetation activity, e.g. about 7% land cover indicated progressive and 4% regressive trend, while 89% land cover exhibited stability (significant at p<0.05) in the LSNP. The progressive trending was likely because of increase in rainfall, while the regressive trending was due to increase in sunlight. The <1% regressive trend observed in classes like sand dunes, sandy/open shrubs, sandy (barren) and open shrubs points toward sustainability of the habitat in the LSNP. The MODIS based VI and time series proved useful in inferring trends in the vegetation activity in this region. Seasonal changes in the habitat of Houbara need regular monitoring and an in-depth research in context of future changes in climate and land use. A participatory approach based on concerted efforts would be effective in conserving this precious bird and its habitat on long-term basis in the region in future.